On the edge: U-Pb, Lu-Hf, and Sm-Nd data suggests reworking of the Yilgarn craton margin during formation of the Albany-Fraser Orogen - Kirkland, Chris; Spaggiari, C.; Pawley, M.; Wingate, M.; Smithies, R.; Howard, H.; Tyler, I.; Belousova, E.; Poujol, M. (2011)
The Albany-Fraser Orogen is considered to be a response to Mesoproterozoic continent–continent collision between the combined North and West Australian Cratons and the combined East Antarctic and South Australian Cratons. However, the tectonic history of the orogen and its components remain enigmatic. Recently, the Kepa Kurl Booya Province has been defined as the crystalline basement of the orogen and divided into the Fraser, Biranup, and Nornalup Zones. New geochronology shows that the Biranup Zone includes 1710–1650 Ma granitic to gabbroic intrusions and is a substantial crustal component extending at least 1200 km along the southern and southeastern margins of the Yilgarn Craton. Previous models interpreted the Biranup Zone as an exotic terrane accreted to the Yilgarn Craton during Mesoproterozoic collision, but new data presented here indicate a strong link to the craton margin during the Paleoproterozoic.Proterozoic magmatism commenced in the Biranup Zone at 1708 ± 15 Ma with metasyenogranite emplacement. This granite has ɛHf values of −10 to −8 and whole rock ɛNd of −15, consistent with a reworked Archean Yilgarn source. Volcaniclastic deposition in the Biranup Zone occurred at 1689 ± 6 Ma, and was rapidly followed by granitic intrusion at 1686 ± 8 Ma. Deformation during the Zanthus Event is constrained by 1676 ± 6 Ma folded migmatitic leucosomes and 1679 ± 6 Ma cross-cutting axial planar leucosomes. A younger suite of granitic and gabbroic rocks, which exhibit distinct mingling and hybridization textures, is dated at 1665 ± 4 Ma. Magmatism in the eastern Biranup Zone displays high-K, calc-alkaline chemistry and a trend towards more juvenile compositions from 1710 to 1650 Ma. Based on the rapidly evolving tectonomagmatic history, modification of the original Yilgarn-like source by juvenile material, and the geochemical evolution of the melts, a feasible tectonic scenario for the Biranup Zone is an arc to back-arc setting on the active Yilgarn Craton margin. Such a model is supported by the 2684 ± 11 Ma magmatic crystallization age of an isolated Archean fragment, which has clear Yilgarn affinity, within the Biranup Zone.The region was subsequently compressed and tectonically dismembered during Stages I (1345–1260 Ma) and II (1215–1140 Ma) of the Albany-Fraser Orogeny. Stage I was dominated by voluminous mafic and granitic magmatism, represented by the Fraser Zone intrusions and the Recherche Supersuite. Two granites from the Fraser Zone, dated at 1298 ± 4 Ma, have ɛHf values overlapping Biranup Zone compositions, indicative of a reworked Biranup source. The Biranup Zone was dominated by granulite facies metamorphism during Stage II. Zircons from the northeastern edge of the Fraser Zone are overgrown by two generations of zircon rims. The earlier rims, at c. 1270 ± 11 Ma, are broken and overgrown by a low-uranium fracture-filling phase at 1193 ± 26 Ma. This indicates uplift and brittle deformation between Stages I and II.